Reflection of Identity through the Use of Bintil Language in Gaya Lentera Muda Community Lampung (Universitas Negeri Semarang, 2017)
Effeminate language reflects effeminate characters and creativity of Gaya Lentera community. Therefore, the effeminate language represents the creative forms of language slang words are fascinating, brief, and simply-recalled. This research found the difference among Gay, Effeminate Men, and LSL [men sex with men] is only at their intonation when they are stating the language. Because through the intonation, they give their intention. There are 42 words examples which are usually used in the community, like: Eke Senandung sama Kanua, Apa kabose, Banjaran, Benyong, Bodrek, Barbie, Pepsi/Kencana wungu, Centong, Capcus, Dese, Duta, Endul/Endang, Gedung, Gilda/Gilingan, Hitachi/Puput melati, Greton/Gretongan, Inang, Eim/Ember/Um, Jalinan kasih, Jengong, Lagi apose, Lapangan bola, and Tandus. Bintil language among Gay, Transgender and LSL is commonly used in everyday life.